Membangun Niat Menggunakan Aplikasi Keuangan Digital pada Guru Slta di Kabupaten Bantul - Muhammad Zaky Sadewa; Heru Tri Sutiono; Dyah Sugandini (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The development of digital financial technology has driven changes in the behavior of educators in managing transactions, necessitating an understanding of the factors that influence their intention to use such applications. This study aims to analyze the role of Customer Satisfaction as a key variable in mediating the influence of Facilitating Conditions, Perceived Security, and Social Influence on the Behavioral Intention of high school teachers in Bantul Regency. The research method used a quantitative approach with Structural Equation Modeling based on Partial Least Squares (SEM-PLS) analysis techniques. Data were obtained by distributing questionnaires to 450 teachers who were the research respondents. The analysis results showed that Customer Satisfaction was the main determinant of Behavioral Intention, with the strongest influence in the model. Facilitating Conditions were found to have a direct effect on Behavioral Intention, but did not increase satisfaction. Meanwhile, Perceived Security and Social Influence did not have a direct effect on Behavioral Intention, but significantly increased Customer Satisfaction, thus becoming full mediators. These findings confirm that the success of digital financial application adoption is mainly influenced by positive user experience, not just facilities, security, or social influence alone.